Zur Rezeption Wolf Biermanns in den beiden deutschen Staaten - Król, Wojciech (Studia Germanica Posnaniensia, 2018)
The author presents negative aspects of cultural politics in East and West Germany on the example of the biography and reception of the Wolf Biermann's works. The first two parts of the article include examples of several sophisticated methods which served as means of repression towards the writer in East Germany. Among other methods there were: prevention from being published and from giving live perfomances, suppression of travelling abroad, correspondence confiscation, vexation of his family and friends with interference in private and intimatest spheres of life, continuous eavesdropping and control, trials of intimidation and the expulsion from East Germany in 1976. The suppressions were continued „succesfully“ also after 1976, during his stay in the West. A part of those „operational activities“ against the poet and his work is documented in „Stasi“ archives, which were made accessible to him 1993 (the documentation about his person includes over 40 000 pages). The last part of the article describes the history of the poet's reception in West Germany either before his expulsion from East Germany or later. The mechanism of the censorship worked there quite differently but it is possible to proove on selected examples, that for instance big, recognized publishers were afraid to publish the damned and oppressed by the East German regime artists.